Kepemimpinan Kepala Sekolah dalam Meningkatan Kualitas Guru: Dampak Pengembangan Profesionalisme terhadap Kurikulum Merdeka - Widi Astutik; Enik Setiyowati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This qualitative case study at SDN Kalipang 1 aims to examine the strategic role of principal leadership in managing teacher resources and to determine the impact of teacher professional development programs on the implementation of the Independent Curriculum at the school level. In-depth interviews with the principal and examination of school documents such as the School Activity and Budget Plan (RKAS) and the Education Report were also used to collect the necessary data. According to field findings, the principal defines teachers as role models using a visionary-instructional leadership paradigm. The Education Report serves as the primary benchmark for identifying teacher deficiencies in the design of needs-based teacher professionalism program policies. The BOS Performance Fund is effectively allocated to support internal Learning Communities (Kombel) that prioritize the implementation of the Teacher Professionalism Program. Significant improvements in teacher policies in the classroom in creating Independent Curriculum assessments can be observed in classroom procedures, such as the implementation of Positive Discipline and the effective integration of digitalization into learning. These are the impacts of the Teacher Professionalism Program that has been created. The effectiveness of school curriculum transformation is determined by the organized and data-driven leadership of the principal. This has proven effective in integrating the outcomes of teacher professionalism programs into quality classroom learning practices.